Opportunities And Challenges Of Learning To Read And Write Al-Qur'an In Early Childhood At The Quran Education Park - Retni Nur Fauziah Fauziah; Burhan Nudin Burhan (Linguanusa : Social Humanities, Education and Linguistic, 2024)
Introduction to The Problem: This research highlights the importance of Quranic education from an early age and investigates the opportunities and challenges in teaching Quranic reading and writing (BTAQ) at TPA Ulil Albab. Purpose: The study aims to analyze the learning opportunities and challenges in BTAQ for early childhood students at TPA Ulil Albab. Design/methods/approach: This is a qualitative case study involving 4 educators and 4 guardians as informants. Data was collected through observation, interviews, and documentation, and analyzed using an interactive model. Findings: The TPA provides opportunities for students to improve their Quranic reading skills through Iqro' and Sorogan methods. Challenges include weak memory, lack of concentration, difficulty in writing, and lack of cooperation between educators and parents. Solutions involve motivation, rewards, advice, and a supportive environment. Research implications/limitations: The research offers insights into BTAQ learning in early childhood, but its findings might be limited to the specific context of TPA Ulil Albab. Originality/value: This study contributes to understanding the dynamics of early Quranic education and provides practical recommendations for enhancing BTAQ learning experiences.